Tinjauan PP No. 20 Tahun 2021 tentang Kebijakan Hukum Pengelolaan Tanah Terlantar di Indonesia - Abulkhair, Muhammad Farhat; Damayanti, Alfina; Taklima, Musa (Maliki Interdisciplinary Journal, 2025)
Land is one of the strategic resources that has complex social, economic, cultural and legal dimensions in the lives of Indonesian people. As an instrument of national development, land management faces various problems, including land tenure inequality, agrarian conflicts, and abandoned land. Abandoned land is land that has been granted rights by the state but is not utilized according to its designation, causing economic and social losses. To address the problem, the Indonesian government established Government Regulation No. 20 of 2021 as the legal framework for controlling abandoned land. This regulation aims to optimize land utilization through the mechanism of identification, inventory, evaluation, and determination of abandoned land, as well as providing sanctions for rights holders who do not fulfill their obligations. This research analyzes the effectiveness of the Government Regulation in addressing the problem of abandoned land using a normative juridical approach. The main focus is to evaluate the legal mechanism and socio-economic implications of this regulation and identify factors that influence its successful implementation. This study aims to provide recommendations for improving land law policy in Indonesia, so that land management becomes more productive and equitable.